UNDERSTANDING STUDENT LEARNING PATTERNS FOR IMPROVING EDUCATION QUALITY - Ulfa Zakaria; Deswita; Siminto (Adisam Publisher, 2024)
In pursuing and realizing effective learning goals, it is necessary to implement a method so that the desired learning process is achieved, namely by learning effectively. Improving the quality of education will be achieved if the teaching and learning process carried out in the classroom is truly effective and useful for achieving the expected knowledge, attitudes and skills. Because basically the teaching and learning process is the core of the overall educational process, the teacher is one of the important factors in determining the success of the learning process in the classroom. The preparation of learning strategies includes individual, group, guided, leaving and supervision learning patterns. There are components that must be considered in developing learning patterns, including teaching objectives, introduction of initial abilities, the teaching process and assessment of the achievement of teaching objectives. What students apply at home as a learning pattern can also be called home learning activities. The learning patterns used by students in their daily lives are certainly different from each other.